Effectiveness of Role Playing Learning Method In Improving Speaking Skills Elementary School Students - Nur Oktavia Jasama, Venny Surya; Mahendra, Yasinta; Suprapto, Irawan (Berkala Ilmiah Pendidikan, 2026)
Speaking skills are an important competency in Indonesian language learning in elementary schools because they play a role in developing communication skills, self-confidence, and active participation. However, various studies have shown that students' speaking skills have not developed optimally due to teacher-centered learning. This study aims to analyze the effectiveness of the role-playing learning method in improving elementary school students' speaking skills through a Systematic Literature Review (SLR) approach. Literature searches were conducted through the Google Scholar database between 2021 and 2025 using the keywords "role-playing method," "speaking skills," and "elementary school students." Based on the established inclusion criteria, 10 relevant articles were obtained and analyzed through data extraction, quality assessment, and descriptive synthesis. The results of the study indicate that the role-playing method is consistently effective in improving students' ability to express ideas orally, speaking fluency, self-confidence, active participation, and learning motivation. Thus, the role-playing method can be recommended as an innovative and effective learning strategy in developing elementary school students' speaking skills.